Circular Economy Innovation in Zero-Waste Corn Utilization to Enhance Creative Economy and Sustainable Food Security - Masyadi, Masyadi; Surianti, Surianti; Tahir, M Afdal (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
This Community Partnership Program was conducted in collaboration with the Kabuttu Farmers Group in Gattareng Village, Soppeng Regency, on August 10, 2025, and involved 31 participants, including corn farmers and community members. The problem addressed was the low added value of corn products and the underutilization of agricultural waste. Corn was primarily sold as dried kernels at low prices, while waste such as husks, stalks, and cobs was often burned, leading to both income loss and environmental degradation. The program aimed to enhance food security and increase farmers’ income through circular economy principles and a zero-waste approach. Using the Participatory Action Research (PAR) method, the intervention included participatory planning, hands-on training, mentoring, the application of appropriate technology, and structured evaluation. Key activities included product diversification (e.g., corn tempeh and corn oil), waste processing (into compost and briquettes), financial management training, and digital marketing through social media and e-commerce platforms. The outcomes demonstrated measurable improvements. Product diversification increased from three to five processed products, and two new waste-based products (compost and briquettes) were developed. Digital marketing adoption rose from zero to four platforms (Shopee, Tokopedia, Facebook, WhatsApp Business), expanding market reach beyond local boundaries. Financially, farmers' average monthly income increased from IDR 1.53 million to IDR 3.2 million. Management capacity also improved: 60% of participants adopted simple bookkeeping practices and began structured business planning. The program contributed to SDGs 2 (Zero Hunger), 12 (Responsible Consumption and Production), and 13 (Climate Action), demonstrating the effectiveness of integrated, participatory empowerment in transforming rural agriculture sustainably.